Anakinra treatment in multisystemic inflammatory syndrome in children (MIS-C) associated with COVID-19 - Çaǧlayan, Şengül; Sönmez, Hafize Emine; Otar Yener, Gülçin; Baǧlan, Esra; Öztürk, Kübra; Ulu, Kadir; Guliyeva, Vafa; Demirkol, Demet; Çakan, Mustafa; Özdel, Semanur; Bukulmez, Hulya; Aktay Ayaz, Nuray; et al. (Frontiers in Pediatrics, 2022)
Objective The study aimed to report the efficacy and safety of anakinra treatment in patients with the refractory multisystemic inflammatory syndrome in children (MIS-C). Methods This is a cross-sectional retrospective study consisting of pediatric patients diagnosed with MIS-C who were treated with anakinra. Results Among the 378 patients diagnosed with MIS-C, 82 patients (21.6%) who were treated with anakinra were included in the study. The median age of patients was 115 (6-214) months. The median duration of hospitalization was 15 (6-42) days. Sixty patients (73.1%) were admitted to the pediatric intensive care unit. Patients were treated with a median dose of 2.7 mg/kg/day anakinra concomitant with IVIG and steroids. Intravenous anakinra was applied to 12 patients while 70 patients received it subcutaneously. Twenty-eight patients required high dose (4–10 mg/kg/day) anakinra. The median day of anakinra initiation was 2 (1-14) days and the median duration of anakinra use was 7 (1-41) days. No injection site reactions were observed while elevated transaminase levels were detected in 13 patients. Seventy-three patients (89.1%) were discharged without any sequela or morbidity. Seven patients (1.8%) died. Abnormal echocardiographic findings continued in two patients (2.4%) (coronary artery dilatation in one, low ejection fraction in one) at discharge and became normal on the 2nd month. Conclusion Based on the results of the study, anakinra was associated with clinical improvements and was safe for most patients with refractory MIS-C.